Pengaruh Kinerja Keuangan dan Pengungkapan Corporate Social Responsibility terhadap Harga Saham pada Perusahaan Infrastuktur - Roy Budiharjo; Ardio Sagita; Swarmilah Hariani (JUDICIOUS, 2022)
The aim of this research is to analyze the effect of profitability, liquidity, disclosure of corporate social responsibility and company size on stock prices. The population in this study are all Infrastructure Sector Companies listed on the Indonesia Stock Exchange for the period 2016 - 2020. Sampling in this study used a purposive sampling method with the following criteria: (1) Infrastructure sector companies listed on the Indonesia Stock Exchange for the 2016 period - 2020. The data needed in this study were taken from the Indonesian Capital Market Directory (ICMD) 2016-2020. The data collection method used in this study is the documentation method. The statistical test was carried out using the t test and multiple linear regression analysis, which was previously carried out by the classical assumption test. The results of this study indicate that: disclosure of corporate social responsibility has a positive effect on stock prices, while profitability is proxied by return on assets, liquidity is proxied by the current ratio, and company size has no significant effect on stock prices.